The influence of social media on alcohol consumption of mothers of children and adolescents: a scoping review of the literature - Reisdorfer, Emilene; Nesari, Maryam; Krell, Kari; Johnston, Sharon; Dunlop, Randi Ziorio; Chute, Andrea; dos Santos Nogueira de Góes, Fernanda; Singh, Inder (My University, 2023)
Alcohol misuse is a common problem in many countries, where alcohol is often portrayed as a fun and interactive coping strategy for mothers to manage the demands of motherhood. Social media platforms have established themselves as a popular forum for mothers to share information and create an environment in which mothers may be exposed to and influenced by alcohol-related content. Given the increased social acceptance and normalization of drinking among mothers, especially during the recent pandemic, a critical analysis of social media influences on alcohol behaviours and consumption is warranted. A scoping review mapped the evidence on social media influences and alcohol consumption among mothers of children and teenagers younger than eighteen years old. Several databases were consulted, and the evidence was collated into two themes and seven subthemes. Factors related to alcohol consumption in motherhood include (1) community and social support, (2) coping and mental health, (3) motherhood expectations and identity, (4) alcohol consumption, (5) marketing strategies, (6) everyday issues, and (7) social media influence. Numerous social, economic, and health problems are associated with alcohol misuse. The current literature suggests that social media is a powerful tool to disseminate messages about alcohol and normalize mothers’ drinking behaviours.
Keywords: mothers; alcohol drinking; social media; reviews